Steinbeck in Seville, Spain unloading his car. - Unknown:::Creator:::::::::::: (Spain; Seville)
Steinbeck in Seville, Spain unloading his car, a Jaguar he had brought from England. He appears to be standing with a Concierge unloading luggage. Original in safe.